Epethelial presence of Trueperella pyogenes predicts site-level presence of cranial abscess disease in white-tailed deer (Odocoileus virginianus). - Emily H Belser; Bradley S Cohen; Shamus P Keeler; Charles H Killmaster; John W Bowers; Karl V Miller (PLoS ONE, 2015)
Cranial/intracranial abscess disease is an emerging source of significant mortality for male white-tailed deer (Odocoileus virginianus). Most cases of cranial/intracranial abscess disease are associated with infection by the opportunistic pathogen Trueperella pyogenes although the relationship between the prevalence of the bacteria and occurrence of disease is speculative. We examined 5,612 hunter-harvested deer from 29 sites across all physiographic provinces in Georgia for evidence of cranial abscess disease and sampled the forehead, lingual, and nasal surfaces from 692 deer. We used polymerase chain reaction (PCR) to determine presence of T. pyogenes from these samples. We found T. pyogenes prevalence at a site was a predictor for the occurrence of cranial abscess disease. Prevalence of T. pyogenes did not differ between samples from the nose or tongue although prevalence along the forehead was greater for males than females (p = 0.04), particularly at sites with high occurrence of this disease. Socio-sexual behaviors, bacterial prevalence, or physiological characteristics may predispose male deer to intracranial/cranial abscess disease. Determination of factors that affect T. pyogenes prevalence among sites may help explain the occurrence of this disease among populations.